Escogiendo la ley - Goldfarb, Phyllis (2008)
[Editors' note: This refers to the symposium organized by the Miami Law Review.] -- "Originally published in English as 'Picking Up the Law,' University of Miami Law Review 57, no. 3, April 2003, pp. 973-987. The editors thank the author and publisher for permission to translate and publish it in this journal. Spanish translation by María Victoria Alonso, Teaching Assistant of Advanced Constitutional and Procedural Law, Faculty of Law (UBA)."